2018
DOI: 10.1007/s12639-018-0976-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Giardia lamblia infection among general population in Mazandaran Province, north of Iran

Abstract: is the most prevalent intestinal parasites of humans in Iran and other in the world although information on geographical distribution of giardiasis plays significant role in identifying communities at high risk, little attention has been paid to study human giardiasis using geographical information system. Therefore, the aim of the current study was to determine temporal and spatial patterns of human giardiasis distribution to identify possible high risk areas and seasons in northern Iran. A total of 4788 peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…These results were in agreement with that obtained by El-Kowrany et al, (2016)who did a similar study in Gharbia Governorate. Also, similar results were obtained by Siyadatpanah et al, (2018), they studied Giardiasis distribution in Iran.…”
Section: Resultssupporting
confidence: 82%
“…These results were in agreement with that obtained by El-Kowrany et al, (2016)who did a similar study in Gharbia Governorate. Also, similar results were obtained by Siyadatpanah et al, (2018), they studied Giardiasis distribution in Iran.…”
Section: Resultssupporting
confidence: 82%
“…A major advantage of GWR model is the presentation of local variability and local collinearity [77] which are not available in modelling with ANN, SVM and GLM. Local variability for each rural district shows the power of the model in different locations across the study area.…”
Section: Discussionmentioning
confidence: 99%
“…They used local Moran's I and found the city of Amol as a major high-risk area among 15 cities in the province. 18 In another study conducted by Asfaram et al in the same province, the Savadkooh region was identified as a high-risk area in terms of B hominis. 19 There are other studies related to spatial analysis of parasitic diseases in different geographical areas of Iran, most of which conducted in a particular area or province, not the whole country.…”
Section: Introductionmentioning
confidence: 90%